On Eigenvalue Distribution of Random Matrices of Ihara Zeta Function of Large Random Graphs - Khorunzhiy, O. (Журнал математической физики, анализа, геометрии, 2017)
We consider the ensemble of real symmetric random matrices H(n,ρ) obtained from the determinant form of the Ihara zeta function of random graphs that have n vertices with the edge probability ρ/n. We prove that the normalized eigenvalue counting function of H(n,ρ) converges weakly in average as n, ρ→∞ and ρ = o(nα) for any α > 0 to a shift of the Wigner semi-circle distribution. Our results support a conjecture that the large Erdős-Rényi random graphs satisfy in average the weak graph theory Riemann Hypothesis.